Polyandry in the Fruit Fly Bactrocera dorsalis Hendel (Diptera: Tephritidae) - Defiana Prastiti; Suputa Suputa; Y. Andi Trisyono (Universitas Gadjah Mada, 2020)
The Oriental fruit fly, Bactrocera dorsalis (Hendel) is a global pest of a wide variety fruits. Due to its importance, the sterile insect technique (SIT) has raised attention as a safe and sustainable solution to this pest. Successful SIT programs require a comprehensive understanding on the mating behavior of this species. Females of oriental fruit flies are known monandrous which implies that females only mate once with one male. This experiment aimed to confirm that female flies were able to mate more than once with the same (multiple mating) or different males (polyandry) in certain period of time. Four different experiments were conducted to test the hypothesis: receptivity a female to the same male (1) and different males (2) in a cage for 11 days; receptivity a mated female with the same male (3) and different males (4) in a cage for 14 days after the first mating. Results indicated that a part of the female oriental fruit flies was capable to mating more than once with the same or different males.